Animal Production (Poultry, Cattle and Goat-Sheep) in Indonesia: Prospects and Strategic Development - Kusuma Diwyanto; Atien Priyanti; Ismeth Inounu (Indonesian Center for Animal Research and Development, 2005)
Animal production in Indonesia has a remarkably good prospect, as the demand for animal products always increases in line with the increase in human population and national economic development . The high animal industry bargaining status heavily depends upon certain input factors e .g . feed availability, breeding, animal management and health, including innovative technology and other external factors . The approach to improve bargaining position of the animal industry should be carried out under simultaneous approaches within harmonized implementation of support policies at the inter-ministerial level . This should be in line with other internal implementing factors i .e . production efficiency, improved product quality, continuity of supply, and market demand. The prime animal industry profiles suggest that poultry, cattle and sheep/goat industries are prospective if their production management follows the accepted procedures and rules . To respond the developing notion of the livestock sector in Indonesia, there is a heavy need for investment support of the government, farmers/people, and private sector. The policy is the creation of a condusive investment sphere, that is expected to create employment opportunities through raising animals at the input through the marketing subsystems, hence, the development of animal production in Indonesia could answer the heavy threats faced in meeting food security, employment opportunity, people's welfare, creating devisa and national economy . Key words: Animal production, investment, prospect